The effectiveness of family-centered maternity care education on attitudes and behaviours of pregnant women - Adinda Putri Sari Dewi; Umi Laelatul Qomar; Sumarni (Universitas Aisyiyah Yogyakarta, 2024)
Stunting is a state of failure to grow experienced by children under five due to chronic malnutrition, especially in the first 1,000 days of life (HPK). The impact caused by stunting can vary, including physical growth disorders, body metabolic disorders, brain growth and development disorders. In addition, stunting is also at a higher risk of suffering from chronic diseases in adulthood. This study aims to analyze the influence of Family Centered Maternity Care education on the attitude and behavior of pregnant women in stunting prevention. This quantitative research uses a quasi-experimental design with a one-group pre-test and post-test design. Sampling for this study uses a purposive sampling technique. The sample of this study is 38 people who have met the inclusion and exclusion criteria. The instrument used was in the form of a questionnaire for measuring attitudes and behaviors that were tested for validity and reliability. Data analysis using univariate analysis, bivariate analysis using Wilcoxon Test. The results of the study showed that there was an influence of Family Centered Maternity Care education on the attitude and behavior of pregnant women in stunting prevention in the Kebumen area. Family Centered Maternity Care education has been proven to increase the knowledge of pregnant women which ultimately changes the attitude and behavior of pregnant women in stunting prevention. The application of Family Centered Maternity Care education should be considered as a health education method in providing continuous midwifery care as an effort to reduce stunting rates.